Analisis Ketersediaan Air Bersih di Desa Tumbang Datu Kecamatan Sangalla Utara Kabupaten Tana Toraja - Luaran Padang, Darius Darwantri (Journal of Urban Planning Studies, 2024)
Living creatures need water to survive. Water is a very vital need for every individual, because it is useful in supporting life processes on earth. The process of meeting the community's need for clean water is not only oriented to quantity or quantity but also to quality and availability. This research aims to determine the availability of clean water in Tumbang Datu Village, North Sangalla District, Tana Toraja Regency and determine the efforts that can be made to fulfill the availability of clean water. This research uses qualitative methods. The availability of clean water in Tumbang Datu Village, North Sangalla District, Tana Toraja Regency is sufficient to support the daily life needs of the community. Fulfilling the availability of clean water uses springs available in Tumbang Datu Village. Efforts that can be made to fulfill water availability in the future can be done in various ways, such as: building infiltration wells, looking for other sources of water, working together to renovate water networks and storage tanks, building drilled wells, collecting and storing rainwater.